From Motion to Prevention: Evaluating Ergonomic Risks of Asymmetrical Movements and Worker Well-Being in an Assembly Line Work - Sławomir Winiarski; Dorota Molek-Winiarska; Barbara Chomątowska (Applied Sciences)
(1) Background: This study examines the association between asymmetrical movements of an assembly line and machining workers and their overall well-being. The primary aim is to quantify the extent to which asymmetrical movements serve as predictors of work-related musculoskeletal disorders (WMSDs) among these workers and their overall well-being. The study emphasises the predictive relationships between asymmetry metrics and health outcomes. (2) Methods: The study included 86 employees from an automotive manufacturing plant, categorised into machining workers (MWEs) and assembly workers (AWEs). The employment duration spanned from 6 months to 40 years. Inertial motion capture technology was employed alongside the Goldberg 28-item General Health Questionnaire for a retrospective observational analysis and assessment of worker well-being. Movement dynamics were evaluated using a Motion Activity Index (MAI) to measure movement intensity, asymmetry, and quality. (3) Results: The machining group demonstrated nearly double the range of motion (median ROM: 36.6° vs. 25.5°, p = 0.019) and peak angular velocities up to eight times higher (median: 40°/s vs. 5°/s) in lumbar and thoracic rotations compared to the assembly group. Significant differences in ROM and movement speeds were observed (p < 0.001). The MAI showed higher dynamic and symmetrical movements in the machining group (36.6% vs. 25.5%, p = 0.019). No significant mental health issues were identified, aside from complaints related to somatic symptoms. (4) Conclusions: This study highlights significant occupational risks due to movement asymmetry in industrial settings, revealing substantial differences in joint angular displacements, velocities, and accelerations between machining and assembly workers. The findings emphasise the importance of targeted ergonomic interventions to enhance worker well-being and advocate for preventive health measures in occupational environments.